Islamic Finance's Role in Social Equity and Poverty Alleviation: Trends and Gaps - Almabrok F Ahmid (Journal of Islamic Monetary Economics and Finance, 2025)
This study investigates global research trends on the role of Islamic finance in promoting social equity and poverty alleviation. Using bibliometric and content analysis methods, we analyze publications on the subject from Scopus from 1991 to 2025 using Rstudio, VOSviewer and Excel to identify key authors, institutions, and journals and to perform a thematic analysis. The results show increasing academic interest, with publication peaking from 2020 onwards. Leading contributors are M. Kabir Hassan and Universiti Utara Malaysia (UUM) for respectively authors and institutions. Dominant themes include zakat, waqf, Islamic microfinance, and financial inclusion, alongside emerging areas like Islamic fintech and productive zakat. Despite its growth, the field remains fragmented, with gaps in governance, regional representation, and long-term impact assessments. Future research should focus on integrating Islamic finance with national poverty strategies, addressing gender disparities, and leveraging technology for greater financial inclusion. This study provides a comprehensive roadmap for scholars and policymakers, contributing to a deeper understanding of Islamic finance as a tool for fostering social equity and poverty alleviation.